Bacterial indicators and antibiotic resistance of Escherichia coli in groundwater - Gambero, Maria Laura (2017)
The aim of this research was to investigate the groundwater quality in El Barreal basin (Córdoba, Argentina), through bacteriological analysis and antibiotic resistance of fecal bacteria indicators and their relationship with geochemical and land uses characteristics. Groundwater samples were collected in 36 wells and the following parameters were determined: major chemical components, heterotrophic plate counts, total and fecal coliforms, Escherichia coli and Pseudomonas aeruginosa. Antibiotic resistance of E. coli was analyzed using standard methods. The chemical and bacteriological analysis showed that more than 80 % of samples were unfit for human consumption. Bacteriological contamination was significant in 36 % of samples. The multivariate analysis between bacterial and geochemical variables explained local contamination conditions, evidenced by the arrival of bacteria and some typical indicators (NO3-, Cl- y HCO3-) to groundwater. No significant correlation between NO3- and bacterial counts was observed, which let us to interpret that part of NO3- contents can be supplied by inorganic fertilizers. Total and fecal coliforms were linked to a local increase of Cl- and HCO3- and a decrease of pH and dissolved oxygen, indicating the arrival and degradation of organic matter into groundwater. The resistance pattern of total E. coli isolates (n=12) showed that the highest percentages were observed for antibiotics of animal use (ampicillin, tetracycline and cephalothin). The analysis of results revealed the impact of land uses demonstrating that livestock activities are the main punctual contaminant sources in this sedimentary aquifer.